Personality Profile - Upadhyay, Surya Nath (Hydro Nepal: Journal of Water, Energy and Environment, 2016)
In light of ongoing discourses, at present, on water resources and hydropower development in Nepal, HYDRO Nepal felt this an appropriate moment to review some of the personalities who have played important roles in this sector over the past few decades. This time, HYDRO Nepal takes pleasure in presenting the personality profile of Mr. Surya Nath Upadhyay. HYDRO Nepal Journal Journal of Water, Energy and Environment Issue: 19 Page: 68-69